Difficulty in differentiating liver injury from an immune checkpoint inhibitor from chemotherapy - Lou, Shike; Wang, Xiaoyin; Yuan, Fei; Zhao, Gangde; Feng, Mingyang; Ding, Yezhou; Lin, Lanyi; Liu, Kehui; Wang, Xiaolin; Chi, Wanqing; Wang, Hui (Frontiers in Pharmacology, 2024)
This study investigated the potential of immune checkpoint inhibitors (ICIs) combined with chemotherapy as a promising treatment approach for malignancies. This report focuses on a patient with drug-induced liver injury (DILI) following the administration of chemotherapy and ICIs. A 63-year-old patient with non-small cell lung adenocarcinoma (NSCLC) initially underwent knife treatment and subsequently received a combination of chemotherapy comprising bevacizumab and camrelizumab. Due to liver abnormalities, both chemotherapy and ICIs were stopped on day 21. The patient's liver function improved within a month after methylprednisolone treatment. Subsequently, the patient received carboplatin, pemetrexed, and bevacizumab without complications. This finding supported the notion that DILI was likely triggered by the ICI. This case series details a complex instance of DILI resulting from the use of ICIs and pemetrexed/carboplatin. The alignment of the pathological findings and clinical presentation strongly suggested ICI-induced DILI, which was further supported by the definitive response to steroid treatment. This information is important for clinicians, as it emphasizes the importance of closely monitoring liver function and being aware of potential adverse effects associated with ICIs. Such insights contribute to more effective patient care.